PENGARUH KESADARAN MEREK DAN ASOSIASI MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SAMSUNG MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING - Albin Reyhan Nur Wiyanto; Sri Rahayu Tri Astuti (Diponegoro Journal of Management, 2022)
The purpose of this study is to analyze the effect of brand awareness and brand association on purchasing decisions through intention to purchase as an intermediate variable. The population used in this study is Samsung smartphone consumers in the city of Semarang. The number of samples used for this research was 125 respondents. The method of collecting the data is carried out by means of a questionnaire. This research uses Structural Equation Modeling (SEM) analysis technique with AMOS 26.0 analysis. The results of this study indicate that Brand Awareness has a positive and significant influence on Purchase Intention, Brand Association has a positive and significant influence on Purchase Intention, and Purchase Interest has a positive and significant influence on Purchase Decision.